Research of the quality of life and stress level of people with hemophilia in Kazakhstan - Kupeyev, A. R.; Aimaganbetova, O. Kh. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
This article is devoted to the study of quality of life and stress levels in patients diagnosed with hemophilia. Hemophilia is a hereditary disease characterized by a sharp decrease in blood coagulation ability due to the low level of factor 8 or factor 9 in the blood, which manifests itself in the first months or years of life in the form of external bleeding and internal hemorrhage. Early disability, physical dis- abilities limit the adaptation of hemophilia patients in all age groups. Constant fear, anxiety, uncertainty in the future change the structure of the individual. The hallmarks of patients with hemophilia are the presence of an increased level of personal anxiety, depression, low self-esteem, low social activity. The purpose of the study is to study the features of quality of life and the level of stress resistance in patients with hemophilia. The scientific novelty lies in the fact that for the first time in Kazakhstan, the study of the psychological characteristics of patients with hemophilia was carried out, in particular the degree of quality of life and the level of stress. As a result, the quality of life of patients with hemophilia was revealed in such areas as physical and psychological well-being, self-perception, microsocial support, social well-being, as well as subjective self-assessment of their quality of life and their health. Key words: hemophilia, hemophilia patients, coping behavior, stress, quality of life, stress tolerance, resilience.